The efficacy and safety of condoliase for lumbar disc herniation: a systematic review and meta-analysis - Huang, Zeling; Xu, Bo; Liu, Yujiang; Chen, Hua; Cai, Xuefeng; Zhang, Long; Shen, Xiaofeng; Li, Yuwei (Frontiers in Pharmacology, 2023)
Background: Chemonucleolysis is a minimally invasive treatment of lumbar disc herniation (LDH). However, the low specificity of the enzyme and the existence of serious adverse events limit the application of chemonucleolysis. Clinical studies in recent years have shown that Chondroitin sulfate ABC endolyase (condoliase) is a potential therapeutic enzyme for LDH. Aim. A meta-analysis was conducted to determine the efficacy and safety of condoliase in LDH treatment. Methods: We searched Web of Science, Embase, PubMed, and Cochrane Library databases. Two reviewers independently screened articles, extracted data, and assessed the risk of bias. The outcomes were the total effective rate, Oswestry Disability Index (ODI) score change, the proportion of lumbar surgery after condoliase treatment, herniated mass volume change, Pfirrmann grade change, and adverse events. Review Manager 5.3 and Stata 12.0 were used for meta-, sensitivity, and bias analysis. Results: Ten studies were included. A single-arm meta-analysis showed that the total effective rate was 78% [95% confidence interval (CI) 75%–81%], the proportion of surgery was 9% (95% CI 7%–12%), the proportion of Pfirrmann grade change was 43% (95%CI 38%–47%), and the adverse events were 4% (95%CI 2%–6%) after condoliase treatment. The two-arm meta-analysis showed that the ODI score change [standard mean deviation (SMD) -2.46, 95%CI -3.30 to -1.63] and the herniated mass volume change (SMD -16.97, 95%CI -23.92 to -10.03) of the condoliase treatment group were greater than those of the placebo control group, and there was no difference in adverse events between the two groups (OR 1.52, 95%CI 0.60 to 3.85). The results of sensitivity and publication bias analyses showed that the results were robust. Conclusions: Condoliase intradiscal injection has excellent eutherapeutic and safety for LDH, thus, has considerable potential as a treatment option besides conservative treatment and surgical intervention for LDH.